Avaliação dos efeitos anticancerígenos dos 1,2,3-triazóis derivados do núcleo 1,4-naftoquinona em linhagens leucêmicas humanas - Coulidiati, Tangbadioa Herve (2014)
The triazole nucleus and its derivatives have attracted considerable attention in recent decades for their chemotherapeutic potentials. Specifically, the interest in molecules containing the 1,2,3-triazole as chemotherapeutic agents for various diseases has increased, because they are known to exhibit a wide range of biological activities, such as anti-proliferative and anti-neoplastic. The aim of this study was to evaluate the potencial anti-cancer effect of new triazole derivatives from 1,4-naphthoquinone, elucidating their cytotoxicity and cell death mechanisms involved. From five cancer cell lines tested, leukemic cells (HL-60 and K562) were the most sensitive, and between the eight triazole compounds tested (called C1 to C8), compounds C2 and C3 showed the best IC50 of 14 μM and 41 μM for HL-60 cells and 24 μM and 81 μM for K562 cells, respectively. However, these two compounds showed very little cytotoxic effect towards PBMC normal cells with IC50 superior to 80 μM. Investigating the type of cell death induced by compounds C2 and C3, it was showed that compounds induced apoptosis in HL-60 cells and cell cycle arrest in the S-phase, and necrosis in K562 ones. Cell cycle arrest in S phase was related to the expression of the p21 gene in K562. Results revealed a reduced expression of Bcl-2 protein and an increased expression of BAX protein in HL-60 cells. Moreover, it was found cytochrome c release, suggesting involvement of the intrinsic pathway in apoptosis induction in these cells. Activation of this pathway may be through inhibition of ERK phosphorylation. Our results also showed that pre-treatment of HL-60 cells with N-acetyl cysteine (1 mM) for 1 hour reduced the cytotoxic effect of compounds C2 and C3 for 30,83% and 26,47% respectively; indicating that the induction of apoptosis in HL-60 is mediated by increased production of intracellular ROS. Thus, it can be concluded that C2 and C3 compounds showed cytotoxic effects on HL-60 and K562 cells, so, can be considered as prototype anti-leukemic molecules.